3D Printing for Chemical Process Laboratories I: Materials and Connection Principles. Issue 3 (8th February 2018) - Gelhausen, Marius Gerrit; Feuerbach, Tim; Schubert, Ansgar; Agar, David William
Abstract: The fabrication of milliliter‐scale test structures for chemical process laboratories with a low‐cost 3D printer operating according to the principle of fused filament fabrication is evaluated. Different polymers such as polypropylene and poly(vinylidene fluoride) were used and fabrication guidelines are provided. Furthermore, reversible and irreversible concepts for connecting 3D‐printed parts to peripherals or to other additively manufactured parts are described. After fabrication, the structures were tested for gas tightness, which was limited without subsequent finishing due to the layer‐wise fabrication process. However, gas tightness up to 600 kPa was attained by using tools like sealing tape. Finally, the developed concepts were extended to permit the insertion of thermoelements or other metallic probes. Abstract : Geometries of different industrial polymers were generated by fused filament fabrication. Chemical, mechanical, and thermal properties as well as guidelines for gastight 3D prints are provided. Reversible and irreversible concepts for connecting 3D‐printed parts to peripherals or to other additively manufactured parts are examined. Gas tightness up to high overpressure was achieved reproducibly.